Expressão antigênica em carcinomas do plexo coróide humano: relato de dois casos - Almeida, M. C.; Bacchi, Carlos Eduardo [UNESP]; Queiroz, L. S.; Facure, N. O. (Academia Brasileira de Neurologia (ABNEURO), 1990)
Neoplasias provenientes do epitélio de revestimento do plexo coróide são inco-muns, tendo sido descritos 6 padrões morfológicos. O padrão anaplásico, também denominado carcinoma do plexo coróide, é o de menor freqüência e pode dar metastases fora do SNC. A distinção histológica desses tumores, particularmente da variedade anaplásica, com outras neoplasias primárias e metastáticas no SNC pode ser difícil. O uso de técnicas imunocitoquimicas em parafina tem-se mostrado útil no esclarecimento das linhagens tumorais. Os papilomas do plexo coróide têm, no entanto, sido objeto de controvérsia, por sua complexa expressão antigênica. Usando a técnica de imunoperoxidase (sistema avidina-biotina-peroxidase) pesquisaram-se, em dois casos da variedade anaplásica, os seguintes marcadores: proteína glial fibrilar ácida (GFAP) com anticorpo monoclonal e policlonal; ceratinas de 40-50kDa, ceratinas de 60-70kDa (callus ceratina), enolase neuronal específica (NSE) e proteína S-100, com anticorpos monoclonais. Os dois tumores mostraram positividade para NSE, proteína S-100 e ceratina de 40-50kDa; uma das duas neoplasias mostrou diferenciação glial, revelando positividade para GFAP tanto com anticorpo monoclonal quanto policlonal.

Primary neoplasms of choroid plexus are rare. Six morphological variants have been described: papillary, cystic, acinar, mucus-secreting, oncocytic, and anaplastic. The anaplastic variant, the so-called choroid plexus carcinoma, is the rarest of all and can metastasize. The differential diagnosis of the anaplastic variant of choroid plexus neoplasms with adenocarcinomas, melanomas and indifferentiated neoplasms can be troublesome chiefly in adults. The now large use of immunocytochemical techniques in tissue section has become a powerful tool in the analysis of cell lineages, tumoral and non-tumoral. Nevertheless, the choroid plexus neoplasms have shown a complex and a somewhat confusing pattern of antigenic expression. In two choroid plexus carcinomas (one localized in the right lateral ventricle from a boy of 1 year and 9 months old, and the other localized in the left lateral ventricle from a girl of 3 years old) the following antigens were searched (using the avidin-biotin-peroxydase complex): glial fibrillary acidic protein (GFAP) with monoclonal and polyclonal antibodies; cytokeratins of 40-50kDa, cytokeratins of 60-70kDA (callus cytokeratin), neuronal specific enolase (NSE) and S-100 protein with monoclonal antibodies. The two neoplasms showed immunoreactivity against NSE, S-100 protein and cytokeratin of 40-50kDA The neoplasm of the boy exhibited glial differentiation having immunoreactivity against GFAP with monoclonal and polyclonal antibodies.
Antigenic expression in human choroid plexus carcinoma: report of two cases